Radio wave propagation in vehicular environments - Azpilicueta, Leyre (The Institution of Engineering and Technology, 2020)
Providing a unified treatment of radio wave propagation in vehicular environments, this book offers a thorough discussion of their theoretical background and fundamental limits, and paves the way to a better understanding of more advanced topics. Further, the book introduces the newest challenges and problems posed by the ever growing need to communicate in mobile networks whilst in a vehicle. The book provides an exhaustive survey of current propagation models, setting a theoretical path that will allow practical engineers and researchers to understand and improve existing wireless mobile networks through better understanding of propagation modelling as applied to the vehicular environment. Chapters are included on wireless channel properties for vehicular environments; modelling and simulation of vehicular communications; intra-vehicle and inter-vehicle short-range wireless channel characterization; vehicular communications channel modelling; and wireless communication system optimization. The book concludes with a chapter exploring applications and case studies. Radio Wave Propagation in Vehicular Environments is suitable for master's students and above in signal processing and mobile communications courses, as well as researchers working in vehicular communications.